Exploring Students Use of Facebook in Formal Learning Contexts - Nagaletchimee Annamalai (Indonesian Journal of EFL and Linguistics, 2017)
This qualitative study aims to explore the use of Facebook environment in narrative writing. Data were collected from students’ narrative writing and focus group interview. The essays were analysed based on Spandel Assessment Scale (2005).The findings revealed that eventhough  students improved their narrative writing, there was lack of in-depth discussion to construct knowledge. It further  proposed that teacher needs to facilitate and guide students as time, space and resources are available online. The students indicated that Facebook was beneficial as it was a convenient  and engaging writing platform. Students also pointed the availability of web-resources to enhance their writing.There were more positive experiences and fewer negative experiences. Limitations of the study were also discussed along with suggestions for future research.